The African diaspora : a musical perspective - Monson, Ingrid T. (Ingrid Tolia) (Critical and cultural musicology, 2003)
African Diaspora presents musical case studies, from various regions of the African diaspora, including Africa, North America, and Europe, that engage with broader interdisciplinary issues about race, gender, politics, nationalism and music.